Studies of freshwater cyanobacteria strains from an ecological perspective in the western region of Saudi Arabia: Studies of freshwater - F Ali, Esmat (Journal of King Abdulaziz University-Meteorology Environment and Arid Land Agriculture Sciences, 2024)
A class of photo-oxygenic bacteria known as cyanobacteria, or blue green algae, can be found from pole to pole in aquatic, aerophytic, and terrestrial environments. They are some of the most common species on Earth and belong to one of the oldest prokaryotic lineages. Only a little amount of research on cyanobacterial strains was conducted in the central and southern regions. This cyanobacteria cological study is thought to be the first in the Kingdom of Saudi Arabia's western region. From this vantage point, the identification of cyanobacteria strains, their physical and chemical characteristics, and the impact of salinity in this area will take precedence. There are two primary components to the current research. The isolated strains were defined and isolated in the first section. The physical and chemical properties are examined in the second section.